Development finance for universal energy access - Giorgio Gualberti; Morgan Bazilian; Erik Haites; Maria da Graça Carvalho (Fondazione Eni Enrico Mattei (FEEM), 2012)
The United Nations General Assembly declared 2012 the International Year of Sustainable Energy for All, officially recognising the urgent need to put energy at the centre of the global development agenda. In parallel, a strong international policy effort is being made to achieve the goal of universal energy access to modern energy services by 2030. To support these efforts, a dramatic scaling-up of financing to the energy sector will be required through official development aid, other official flows, climate financing and various private flows. In this paper we analyse the recent evolution of development policies and finance for the energy sector using both descriptive and analytical tools. We find that, although development finance for the energy sector rose considerably during the past decade, the financial flows have not been directed towards the countries with the lowest levels of energy access.
Keywords: F35; Q40; O20; 330; Development Finance; Energy Policy; Energy Access